Association between polymorphisms in NOBOX and litter size traits in Xiangsu pigs - Huang, Jiajin; Ruan, Yong; Xiao, Meimei; Dai, Lingang; Jiang, Chuanmei; Li, Jifeng; Xu, Jiali; Chen, Xiang; Xu, Houqiang (Frontiers in Veterinary Science, 2024)
The newborn ovary homeobox gene (NOBOX) regulates ovarian and early oocyte development, and thus plays an essential role in reproduction. In this study, the mRNA expression level and single nucleotide polymorphism (SNP) of NOBOX in various tissues of Xiangsu pigs were studied to explore the relationship between its polymorphism and litter size traits. Also, bioinformatics was used to evaluate the effects of missense substitutions on protein structure and function. The results revealed that NOBOX is preferentially expressed in the ovary. Six mutations were detected in the NOBOX sequence, including g.1624 T>C, g.1858 G>A, g.2770 G>A, g.2821 A>G, g.5659 A>G, and g.6025 T>A, of which g.1858 G>A was a missense mutation. However, only g.1858 G>A, g.5659 A>G, and g.6025 T>A were significantly associated with litter size traits (p < 0.05). Further prediction of the effect of the missense mutation g.1858 G>A on protein function revealed that p.V82M is a non-conservative mutation that significantly reduces protein stability and thus alters protein function. Overall, these findings suggest that NOBOX polymorphism is closely related to the litter size of Xiangsu pigs, which may provide new insights into pig breeding.